The incidence and management of slipped capital femoral epiphysis: a population-based study - Ripatti Liisi; Kauko Tommi; Kytö Ville; Rautava Päivi; Sipilä Jussi; Lastikka Markus; Helenius Ilkka (Acta Medica Belgica, 2025)
We aimed to investigate the national trends in the incidence and management of slipped capital femoral epiphysis (SCFE) and to report the need for reoperations.
We included all <19-year-old patients hospitalised for SCFE in 2004-2014 in mainland Finland (n=159). Data from the Finnish Care Register for Health Care, Statistics Finland, and Turku University Hospital patient charts were analyse for the incidence of SCFE in 2004-2012, the length of stay, and the type of surgery with respect to age, gender, study year, and season. The reoperations and rehospitalisations in 2004-2014 for SCFE were analysed for 2-10 years after surgery. In 2004 to 2012, primary surgery for SCFE was performed for 126 children. The average annual incidence of SCFE was 1.06/100 000 (95% confidence interval [CI], 0.81-1.38) in girls and 1.35/100 000 (95% CI 1.07-1.70) in boys. The median age at surgery was lower in girls than in boys (11 and 13 years, respectively, p<0.0001). During the study period, there was no significant change in the incidence of SCFE (p=0.9330), the type of primary procedures performed (p=0.9988), or the length of stay after the primary procedure (p=0.2396). However, the length of stay after percutaneous screw fixation was shorter compared with open reduction and fixation (mean 3.4 and 7.9 days, respectively, p<0.0001). There was no significant difference in the rate of reoperations according to the type of primary surgery.
In conclusion, the incidence of SCFE and the proportion of different primary surgeries have recently remained stable in Finland.